Dual Action of Mexiletine and Its Pyrroline Derivatives as Skeletal Muscle Sodium Channel Blockers and Anti-oxidant Compounds: Toward Novel Therapeutic Potential - De Bellis, Michela; Sanarica, Francesca; Carocci, Alessia; Lentini, Giovanni; Pierno, Sabata; Rolland, Jean-François; Conte Camerino, Diana; De Luca, Annamaria (Frontiers in Pharmacology, 2018)
Mexiletine (Mex) has been recently appointed as an orphan-drug in myotonic-syndromes, being a potent use-dependent blocker of skeletal-muscle sodium channels (NaV1.4). Available evidences about a potential anti-oxidant effect of Mex and its tetramethyl-pyrroline-derivatives in vivo, suggest the possibility to further enlarge the therapeutic potential of Mex-like compounds in myopathies in which alteration of excitation-contraction coupling is paralleled by oxidative stress. In line with this and based on our previous structure-activity-relationship studies, we synthesized new compounds with a tetramethyl-pyrroline-ring on the amino-group of both Mex (VM11) and of its potent use-dependent isopropyl-derivative (CI16). The compounds were tested for their ability to block native NaV1.4 and to exert cyto-protective effects against oxidative-stress injury in myoblasts. Voltage-clamp-recordings on adult myofibers were performed to assess the tonic and use-dependent block of peak sodium-currents (INa) by VM11 and CI16, as well as Mex. VM11 and CI16 were 3 and 6-fold more potent than Mex in producing a tonic-block of peak sodium-currents (INa), respectively. Interestingly, CI16 showed a 40-fold increase of potency with respect to Mex during high-frequency stimulation (10-Hz), resulting the strongest use-dependent Mex-like compound so far. The derivatives also behaved as inactivated channel blockers, however the voltage dependent block was modest. The experimental data fitted with the molecular-modeling simulation based on previously proposed interaction of main pharmacophores with NaV1.4 binding-site. CI16 and VM11 were then compared to Mex and its isopropyl derivative (Me5) for the ability to protect C2C12-cells from H2O2-cytotoxicity in the concentration range effective on Nav1.4. Mex and Me5 showed a moderate cyto-protective effect in the presence of H2O2, Importantly, CI16 and VM11 showed a remarkable cyto-protection at concentrations effective for use-dependent block of NaV1.4. This effect was comparable to that of selected anti-oxidant drugs proved to exert protective effect in preclinical models of progressive myopathies such as muscular dystrophies. Then, the tetramethyl-pyrroline compounds have increased therapeutic profile as sodium channel blockers and an interesting cyto-protective activity. The overall profile enlarges therapeutic potential from channelopathies to myopathies in which alteration of excitation-contraction coupling is paralleled by oxidative-stress, i.e. muscular dystrophies.